Real Person Fanfiction and the Construction of the (Un)Ethical Fan - Lauren Balser (Persona Studies)
Real person fanfiction (RPF) has a tumultuous history within academia and fandom. Though RPF remains a staple of fandom, the fans that write and read it are often moralised for their alleged misunderstanding of what constitutes a fictional character. Consequently, much of RPF studies focuses on fans’ construction of the celebrity persona. Though important, this focus on celebrity persona is prioritised over the role that RPF plays in constructing the persona of the (un)ethical fan. The act of reading, writing, and discussing RPF is not just about constructing the celebrity persona—it is equally, and always, concerned with constructing and performing the fannish persona, particularly along moral lines. This article uses the Taskmaster fandom as a case study, as the British comedy panel show—whose presenters enact a dominant/submissive dynamic via their Taskmaster personas—blurs the boundary between fiction and reality both on and off the show, making its fannish spaces ripe with discussion of fan ethicality, the construction of (un)ethical celebrity, and fan persona. Simultaneously, Taskmaster’s presenters’ explicit discussion of RPF written about them, and the response of the fandom to this discussion, shines light on how fans view their own moral positionality and how they construct (un)ethical fan personas. In investigating this fandom’s performance of what they call “ethical RPF”, this article seeks to theorise the construction of an (un)ethical fan persona as innately intertwined with RPF as a practice and fans’ treatment of it as moral performance.